Characterization of Enterococcus faecium and Enterococcus faecalis clinical isolates in a Malaysian Hospital - Weng, Poh Leng (2013)
Enterococcus faecium and Enterococcus faecalis have been well documented as ubiquitous, Gram-positive cocci, opportunistic nosocomial pathogens. In recent decades, they have been recognized as the primary agent for nosocomial infections in many countries worldwide. The aims of the study were to determine the molecular characterization of E. faecium and E. faecalis isolated from patients in a Malaysian hospital focused on enterococcal surface protein (esp) gene, biofilm formation, association of esp gene with antibiotic resistance and genetic relatedness amongst the isolates collected. Samples were collected from a local tertiary hospital from May 2009 to March 2010 and subjected to characterization via biochemical identification, antibiotic susceptibitilty tests and DNA extraction. PCR was performed for genotypic identification and esp gene detection and MLST of isolates. Association of biofilm with the presence of esp gene was also examined with crystal violet assay. Enzymatic digestion with SmaI and PFGE typing were used to determine genetic relatedness of some strains. In this study, E. faecalis (n=52) was found to be most commonly isolated amongst 80 isolates followed by E. faecium (n=28). The higher resistance rates were exhibited by E. faecium in decreasing order: tazobactampiperacillin (96.4%), ampicillin (92.9%), high-level gentamicin (89.3%) and penicillin (82.1%). Whereas E. faecalis demonstrated slightly lower resistance rates: high-level gentamicin (25.0%), penicillin (7.7%), ampicillin (1.9%) and tazobactam-piperacillin (1.9%) respectively. No vancomycin and teicoplanin resistant enterococci was found. The prevalence of esp gene was found higher in E. faecium (78.5%) compared to E. faecalis (46.2%). However, the prevalence of this gene was more predominantly found in isolates that were resistant to ampicillin (74.1%) and tazobactam-piperacillin (65.8%). Ampicillin–resistant strains and esp gene were strongly associated with the genetic clustering in clonal complex-17. A significant strength of relationship between esp gene and biofilm formation was strongly observed in E. faecium than in E. faecalis. Some isolates without the esp gene were also found to form biofilms and these findings suggest esp might play a significant role although multiple factors might also be involved apart from environmental conditions. PFGE typing revealed high genetic diversity of enterococcal isolates and no indication of outbreaks. Clonally related ST types (ST6, ST16, ST28, E. faecalis; ST17, ST 78, ST203, E. faecium), which are circulating globally and two new ST types (ST399, E. faecalis; ST601, E. faecium) were obtained via MLST. ST6, ST16, ST28 and ST179 of E. faecalis were documented and of particular concern ST6 is associated with clonalcomplex 2, a representative of hospital adapted complexes and the most often reported amongst hospital isolates ST type. ST type of E. faecium: ST17, ST78 and ST203, have been widely linked to CC17, which is associated worldwide spread and hospital outbreaks. The conclusion drawn from this study is that E. faecium exhibited high resistance rate, which is expected and observed in other countries. Strong association of esp gene with biofilm formation in E. faecium would suggest esp gene as a potential marker for line-associated infections. In addition, detection of several ST types in both species should prompt proper surveillance system to be carried out in the near future.